Studi Literatur : Analisis Efektivitas Model Pembelajaran Inquiri Terbimbing terhadap Motivasi Belajar dan Keterampilan Proses Sains Siswa - Anisa Septi Pratiwi; Pria Nur Wulandari; Nur Kasanah; Vandaria Dewi Cahyani; Rif’ati Dina Handayani; Sri Astutik (Jurnal Ilmiah Wahana Pendidikan, 2023)
Students are required to solve problems, analyze ideas, to implement the knowledge they learn so that learning becomes active. Without the teacher's direction and guidance, students cannot learn independently and cannot be guided towards the best learning process. Optimizing the learning and teaching process and making students' skills in the science process improve requires developments in learning models. This study aims to analyze the effectiveness of the guided inquiry learning model in increasing students' learning motivation and skills in the science process through literature studies by examining some data from previous research articles both at national and international levels. The research method used is theoretical study. The results of the theoretical review (literature review) based on articles 1-8 can be concluded that the application of the guided inquiry learning model can increase student learning interest. According to the average results that have been obtained, the learning motivation of students will increase when given the guided inquiry learning model. Based on the well-known descriptions of articles 1 to 16, it can be seen that the guided inquiry learning model can successfully boost students' learning desires. The conclusion from the analysis of the effectiveness of the guided inquiry learning model on learning motivation and helping students to improve their science process skills. The inquiry learning process is able to develop students' intellectual abilities as well as in solving problems.